Memahami Hak Dan Kewajiban Warga Negara: Sebuah Kajian Perspektif Siswa Melalui Pendekatan Diskusi Kelompok - Vira Permata Sari; Ririn Julian Tika; Try Audyta Rezky Rahmadani (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Although every individual has knowledge about the rights and responsibilities as a citizen to a certain extent, these rights and responsibilities are often neglected due to the busy life in society. Education is very important for every country because it serves as the main marker in assessing the extent to which the country can maintain the welfare, protection, and fulfillment of primary, secondary, and tertiary needs of its citizens. In Indonesia, regulations that establish the right of every citizen to obtain education are regulated in Article 31 paragraph (1) of the 1945 Constitution. The purpose of this discussion is to improve the understanding of society and students about the rights and duties of every citizen in building a good country, as well as to raise awareness of the importance of respecting the rights of others and carrying out their obligations. Therefore, this journal is a qualitative research that uses data collection techniques through group discussions and literature reviews.